PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PENGALAMAN DIKLAT TERHADAP KOMPETENSI PROFESIONAL GURU - Yurnaningsih, Antiek (Universitas Negeri Semarang, 2012)
The purpose of this research is to determine the level of influence between headmaster leader-ship and trainning experience on proffesional competance in senior high school economics/accountancy teachers Kudus ditrict simultaneously and partially. Populations that used in this research is all of the economics/accountancy teachers in senior high school Kudus dis-trict (51 people). Methods of data collection are documentation, questionnaire, and interview. Methods of data analysis is descriptive and hypothesis testing using multiple linear regression analysis. Headmaster leadership and trainning experience simultaneously affect the proffe-sional competance (40,7%), headmaster leadership partially affect the proffesional competance (17,22%) and partially affected the trainning experience of teacher’s proffesional competance (32,26%).